Summary of the Research of Automated Mechanical Transmission - Xu Shanzhen; Wei Minxiang; Wang Cheng (Jixie chuandong)
The significance and value of research on the key technologies of AMT is discussed,and the structural characteristics,performance and application of 3 types of AMT are analyzed. Besides,the research status and achievements of AMT in recent years from the aspects of the design & optimization of shift control system and the design of shift actuator are described. Furthermore,the prospects of the future and development trend of AMT’s research hotspots is carried out. A guiding value in the development of AMT technology is provided.